(untitled) (Journal of Engineering, 2010)
This paper is concerned with the investigation of the optimum period of time between maintenance by the aid of Monte Carlo simulation technique of an old water tube boiler, double identical drums; its capacity is 70 ton/ hour of super heated steam. There are a multitude of failures that are caused by boiler operator’s errors, boiler inspector, boiler maintainer and faults of boiler auxiliary equipments which lead to operation parameter deviations and boiler shut down. Changing maintenance plan to be based on optimum period of time between scheduled maintenance and inspection will achieve maximum boiler availability.